Longitudinal evaluation of the impact of school characteristics on changes in physical activity opportunities - Rajbhandari-Thapa, Janani (PLoS One, 2020)
BACKGROUND: Even as many states adopt physical activity policies to promote physical activity and prevent childhood obesity, little is known about differences in policy implementation based on school characteristics. We studied association of school characteristics and changes in physical activity opportunities at the school level during the implementation of a statewide physical activity policy in the state of Georgia. METHODS: A web-based school survey was administered to elementary schools at two time points (before and during policy execution). Matched respondents (289 classroom teachers, 234 administrators) reported the frequency and duration of recess and integrated physical activity time. We used paired t-test to assess changes in physical activity opportunities and chi-square tests to assess the association of change in physical activity opportunities with school characteristics. We then constructed a multiple linear regression model following a change score method to identify school-level factors that predict the magnitude of change in physical activity opportunities. RESULTS: There was an overall significant increase in total physical activity opportunities across time; however, schools with higher poverty showed a decrease in physical activity time by 5.3 minutes per day (95% CI: -9.2, -1.3). Further, the changes in physical activity time for schools in suburban Georgia were smaller (-5.7, 95% CI: -9.5, -1.9) compared to schools located in towns. CONCLUSIONS: The change in physical activity opportunities was not the same across schools and school characteristics predicted the magnitude of change. Additional efforts at the local level might be needed for equitable policy implementation based on schools’ geographical location and poverty level of the student population.